Sound Absorption Of MPP With Irregular Hole Distribution - Putra, Azma; Jameel, Esraa Al-Amer; Mat Dan, Reduan; Mosa, Ali Ibrahim (IAEME Publication, 2020)
Analytical models for the sound absorption coefficient of MPP are extensively available particularly for the cases where holes are regularly distributed across the MPP structure. The behaviors of sound absorption performance have therefore been well recognized. Thus, it’s also interesting to study the MPP for the cases where the distribution of holes is not spaced regularly across the MPP, which becomes the objective of this paper. Here, the FEM is employed to simulate the acoustic impedance of the panel holes. Two main cases of irregular hole distributions are observed, namely 1) where the holes are concentrated in the middle of the plate, and 2) where the holes are distributed around the edge. For each case, this is applied for MPP with homogenous and inhomogeneous perforations. The analysis reveals that for both cases of hole distributions, the peak absorption can shift to lower frequency with the second case to have more effect than the first case. The finite element models are validated with experiment with good agreement.